Impact of electron-beam irradiation on the quality characteristics of raw ground beef. (June 2019) - Feng, Xi; Jo, Cheorun; Nam, Ki Chang; Ahn, Dong U.
Abstract: The aim of this study was to evaluate the effects of different irradiation doses (0–4.5 kGy) on the quality of raw ground beef. The results showed a significant increase in lipid oxidation and protein oxidation after irradiation, and color fading was observed only at 4.5 kGy irradiation. The increasing spermidine did not trigger any food safety panic button in irradiated raw ground beef, but this issue should be taken into consideration in irradiated cured meat products. Electronic tongue detected higher saltiness in irradiated meat due to increased drip loss by irradiation. Due to the synergistic effect of saltiness on umami, an unexpected increase in umami taste was observed at 4.5 kGy. Dimethyl disulfide produced from the sulfur-containing amino acids, the major irradiation processing biomarker, was only detected at 4.5 kGy irradiation. Thus, electron beam irradiation <4.5 kGy was effective doses for the vacuum-packaged raw ground beef without influencing its physicochemical characteristics. Highlights: A color fading was observed at 4.5 kGy. Nucleotides degradation & biogenic amines increase had minor effect to the off-taste. The increasing biogenic amines didn't trigger any food safety panic button. Irradiation off-odor at 4.5 kGy was correlated to dimethyl disulfide. Lower-dose radiation (≤3.0 kGy) brought limited changes to the sensory profile.